2014 IEEE International Symposium on Information Theory 2014
DOI: 10.1109/isit.2014.6875058
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-aware training and scheduling for the 2-user MISO broadcast channel

Abstract: Abstract-In this paper we study the stability region of the 2-user MISO broadcast channel where the transmitter employs Zero Forcing precoding when both users are scheduled, taking into account the time overheads needed for uplink channel training. We show that, with proper signalling design, combining a decentralized policy with the baseline centralized one for user selection can increase the stability region of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Explicitly, denoting by C N T (x) the average cost obtained over the time duration 0 ≤ t ≤ T under Whittle's index policy conditioned on the initial state x ,we show that C N T (x) tends to C RP,N when N and T scale. The reason behind comparing C RP,N and C N T (x) is that C RP,N is a lower bound of all expected average cost obtained by any policy that resolves the original problem (3). This means that it is sufficient to prove that C N T (x) converges to C RP,N when T and N scale in order to establish the asymptotic optimality of Whittle's index policy.…”
Section: Local Optimalitymentioning
confidence: 99%
“…Explicitly, denoting by C N T (x) the average cost obtained over the time duration 0 ≤ t ≤ T under Whittle's index policy conditioned on the initial state x ,we show that C N T (x) tends to C RP,N when N and T scale. The reason behind comparing C RP,N and C N T (x) is that C RP,N is a lower bound of all expected average cost obtained by any policy that resolves the original problem (3). This means that it is sufficient to prove that C N T (x) converges to C RP,N when T and N scale in order to establish the asymptotic optimality of Whittle's index policy.…”
Section: Local Optimalitymentioning
confidence: 99%
“…Apart from focusing on the receivers and not the precoder at the transmitter, the work in [10] addresses sum rate maximization, so the traffic processes of the users are not taken into account. More in this direction, a recent work [11] showed that feedback policies exploiting the fact that the users know their channel can enlarge the stability region for a two-user system, under the idealized assumption that contention without collisions ispossible.…”
Section: Introductionmentioning
confidence: 99%